POLA DISTRIBUSI JENIS MERANTI (Shorea spp.) DI RESORT PEMERIHAN TAMAN NASIONAL BUKIT BARISAN SELATAN - Riki Prayoga; Indriyanto Indriyanto; Melya Riniarti (Lambung Mangkurat University-Indonesia, 2019)
Pemerihan Resort is one of management unit of Bukit Barisan Selatan National Park (BBSNP). Pemerihan Resort has a variety of plants, including various types of meranti. Currently the data releated to the distribution of meranti at the Pemerihan Resort of BBSNP is not available, so it is necessary to do research on the distribution of meranti at the Pemerihan Resort BBSNP. The objectives of this research to analyze the distribution pattern of meranti in Pemerihan Resort BBSNP. The method used vegetation analyze with compartement line method and analyzed with Importance Value Index (IVI) and Coefecient of Distribution (CD). The results of this research showed in the research sites was dominated by Shorea hopeifolia with Importance Value Index (40.96%). While other meranti species like Shorea javanica, Shorea leprosula, Shorea multiflora, Shorea ovalis, Shorea ovata, Shorea palembanica, and Shorea parvifolia has a low dominance level (0.80 – 7.83%). Distribution pattern of 7 species of meranti is a clumped i.e Shorea hopeifolia, Shorea javanica, Shorea leprosula, Shorea multiflora, Shorea ovalis, Shorea ovata, Shorea parvifolia and Shorea palembanica which had a random distribution pattern.